Sodium glucose co-transporter 2 inhibitors and cardiovascular event protections: how applicable are clinical trials and observational studies to real-world patients? - Ming-Jui Hung; Edward Chia-Cheng Lai; Shih-Chieh Shao; Yi-Han Lin; Kai-Cheng Chang; Yuk-Ying Chan; Yea-Huei Kao Yang (BMJ Open Diabetes Research & Care)
Objective This study evaluated the characteristics of new users of sodium glucose co-transporter 2 inhibitors (SGLT2i) in clinical practice to assess the applicability of the findings from clinical trials (Empagliflozin, Cardiovascular Outcomes and Mortality in Type 2 Diabetes (EMPA-REG OUTCOME) trial, Dapagliflozin Effect on Cardiovascular Events (DECLARE)-TIMI 58 trial, Canagliflozin Cardiovascular Assessment Study (CANVAS) program and the Evaluation of Ertugliflozin Efficacy and Safety Cardiovascular Outcomes (VERTIS-CV) trial) and multinational observational studies (CVD-REAL Nordic study and CVD-REAL 2 study).Research design and methods We conducted a retrospective cohort study using the largest electronic medical records database from seven hospitals in Taiwan. We included adult patients with type 2 diabetes initiating canagliflozin, dapagliflozin and empagliflozin between 1 January 2018 and 31 August 2019. We compared the patient characteristics with SGLT2i to examine the data representativeness of clinical trials and to evaluate channeling uses between canagliflozin, dapagliflozin and empagliflozin.Results We identified a cohort of 11 650 patients newly initiating SGLT2i, 49.9% of whom received empagliflozin. However, only 18.7%, 19.2%, 50.4% and 57.3% of real-world SGLT2i new users were included in the EMPA-REG OUTCOME trial, VERTIS-CV trial, DECLARE-TIMI 58 trial and CANVAS program, respectively. Reasons for exclusion were largely reduced cardiovascular disease risks in real-world patients, namely 72.8%, 73.6% and 34.2% for EMPA-REG OUTCOME trial, VERTIS-CV trial and DECLARE-TIMI 58 trial and CANVAS program, respectively. However, hemoglobin A1c out of range accounted for the most frequent reason (25.0%) for exclusion of real-world patients from the CANVAS program. We found channeling uses in different SGLT2i, for example, more patients receiving empagliflozin (15.3%) and canagliflozin (19.6%) had poorer renal functions (eg, estimated glomerular filtration rate <60 mL/min/1.73 m2), compared with dapagliflozin (9.3%).Conclusions The findings provide clear evidence that results from current studies may be less applicable to real-world patients. Further studies are required to support the concept of real-world cardiovascular event protection through SGLT2i.